Status and Influencing Factors of Parenteral Nutrition Practice for Late Preterm Infants in China - Quan, Meiying; Li, Zhenghong; Wang, Danhua; Schibler, Kurt; Yang, Li; Liu, Jie; Qin, Xuanguang; Zhang, Xin; Han, Tongyan; Li, Ying (Frontiers in Pediatrics, 2022)
Objectives To explore the status of parental nutrition practice of hospitalized late preterm infants and the factors influencing the clinical prescription. Methods A multi-center, prospective cohort study was conducted during October 2015 to October 2017. Infants born after 34 weeks and before 37 weeks were enrolled from twenty-five hospitals in the Beijing area of China. Data of enteral and parenteral nutrition were collected. Results A total of 1463 late preterm infants were enrolled in this study, 53.9% of infants were supported by parenteral nutrition. Over 60% of 34 weeks’ infants were on parenteral nutrition during the 2nd to the 4th day. Logistic regression analysis showed that gestational age(GA) (OR=0.66, 95%CI 0.58-0.81), birth weight (OR=0.99, 95%CI 0.99-1.00), hypoglycemia (OR=0.37, 95%CI 0.25-0.54), small for gestational age (SGA) (OR=0.45, 95%CI 0.28-0.75), feeding intolerance (OR=0.18, 95%CI 0.05-0.60), neonatal respiratory distress syndrome (NRDS) (OR=0.41, 95%CI 0.21-0.81), neonatal infection(OR=0.60, 95%CI 0.44-0.82), and slow enteral nutrition advancement rate (OR=0.92, 95%CI 0.90-0.95) were factors influencing the administration of parenteral nutrition. Conclusions Over half of hospitalized late preterm infants were prescribed with parenteral nutrition. Infants with lower GA, lower birth weight, diagnosed with hypoglycemia, SGA, feeding intolerance, NRDS, neonatal infection, or a slower rate of enteral nutrition advancement had a higher likelihood of receiving parenteral nutrition.